Dendritic cells of mesenteric and regional lymph nodes contribute to Yersinia enterocolitica O:3-induced reactive arthritis in TNFRp55-/- mice - Silva, Juan Eduardo (2020)
Dendritic cells (DCs) participate in the pathogenesis of several diseases. We investigated DCs and the connection between mucosa and joints in a murine model of Yersinia enterocolitica O:3-induced reactive arthritis (ReA) in TNFRp55-/- mice. DCs of mesenteric lymph nodes (MLN) and joint regional lymph nodes (RLN) were analyzed in TNFRp55-/- and wild-type mice. On day 14 after Y. enterocolitica infection (arthritis onset), we found that under TNFRp55 deficiency, migratory (MHChighCD11c+) DCs increased significantly in RLN. Within these RLN, resident (MHCintCD11c+) DCs increased on days 14 and 21. Similar changes in both migratory and resident DCs were also detected on day 14 in MLN of TNFRp55-/- mice. In vitro, LPS-stimulated migratory TNFRp55-/- DCs of MLN increased IL-12/23p40 compared with wild-type mice. In addition, TNFRp552/2 bone marrow-derived DCs in a TNFRp55-/- MLN microenvironment exhibited higher expression of CCR7 after Y. enterocolitica infection. The major intestinal DC subsets (CD103+CD11b-, CD103-CD11b+, and CD103+CD11b+) were found in the RLN of Y. enterocolitica-infected TNFRp55-/- mice. Fingolimod (FTY720) treatment of Y. enterocolitica-infected mice reduced the CD11b- subset of migratory DCs in RLN of TNFRp55-/- mice and significantly suppressed the severity of ReA in these mice. This result was associated with decreased articular IL-12/23p40 and IFN-g levels. In vitro FTY720 treatment downregulated CCR7 on Y. enterocolitica-infected bone marrow-derived DCs and purified MLN DCs, which may explain the mechanism underlying the impairment of DCs in RLN induced by FTY720. Taken together, data indicate the migration of intestinal DCs to RLN and the contribution of these cells in the immunopathogenesis of ReA, which may provide evidence for controlling this disease.